Design, synthesis, antileishmanial, and antifungal biological evaluation of novel 3, 5‐disubstituted isoxazole compounds based on 5‐nitrofuran scaffolds. Issue 2 (16th December 2019) - Trefzger, Ozildéia S.; Barbosa, Natália V.; Scapolatempo, Renata L.; das Neves, Amarith R.; Ortale, Maria L. F. S.; Carvalho, Diego B.; Honorato, Antônio M.; Fragoso, Mariana R.; Shuiguemoto, Cristiane Y. K.; Perdomo, Renata T.; Matos, Maria F. C.; Chang, Marilene R.; et al.
Abstract: Nineteen 3, 5‐disubstituted‐isoxazole analogs were synthesized based on nitrofuran scaffolds, by a [3 + 2] cycloaddition reaction between terminal acetylenes and 5‐nitrofuran chloro‐oxime. The compounds were obtained in moderate to very good yields (45–91%). The antileishmanial activity was assayed against the promastigote and amastigote forms of Leishmania (Leishmania) amazonensis . Alkylchlorinated compounds 14p–r were active on both the promastigote and amastigote forms, with emphasis on compound 14p, which showed strong activity against the amastigote form (IC50  = 0.6 μM and selectivity index [SI] = 5.2). In the alkyl series, compound 14o stands out with an IC50  = 8.5 μM and SI = 8.0 on the amastigote form. In the aromatic series, the most active compounds were those containing electron‐donor groups, such as trimethoxy isoxazole 14g (IC50  = 1.2 μM and SI = 20.2); compound 14h, with IC50  = 7.0 μM and SI = 6.1; and compound 14j containing the 4‐SCH3 group, with IC50  = 5.7 μM and SI = 10.2. In addition, the antifungal activity of 19 nitrofuran isoxazoles was evaluated against five strains of Candida ( C. albicans, C. parapsilosis, C. krusei, C. tropicalis, and C. glabrata ). Eleven isoxazole derivatives were active against C. parapsilosis, and compound 14o was found to be the most active (minimal inhibitory concentration [MIC] = 3.4 μM) for this strain. Compound 14p was active against all the strains tested, with an MIC = 17.5 μM for C. glabrata, lower than that of the fluconazole used as the reference drug. Abstract : Nineteen 3, 5‐disubstituted isoxazole analogs were synthesized based on 5‐nitrofuran scaffolds and evaluated against the promastigote and amastigote forms of Leishmania amazonensis and against Candida species. Alkylchlorinated compounds 14p–r were active on both promastigotes and amastigotes and 11 isoxazole derivatives showed activity against C. parapsilosis .